Proposta de desenvolvimento e implementação de ferramenta mobile para realização de exame fonético fonológico - VALENTE, Victória Larissa Souza (2019)
It is noticeable how technology is being largely inserted in different environments, such as hospital, educational or business. It is provided an increasingly facility and agility by computerizing processes, which were previously accomplished manually, bringing satisfactory results, higher productivity, sustainability - due to the decrease of paper usage - and technological globalization. The phonetic and phonological exam is conducted by phonoaudilogists, and it enables tracking, analysis and diagnosis of phonological disturbances in children, adolescents and adults. The proposal of developing a mobile appliance, during a period of initial use, in Android devices emerged on the need of reducing a huge amount of paper used to diagnose patients, and also considering the difficulty to store, for further analysis, results after medical appointment.